2022
DOI: 10.1002/aoc.6742
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable synthesis of highly diastereoselective & fluorescent active spirooxindoles catalyzed by copper oxide nanoparticle immobilized on microcrystalline cellulose

Abstract: Composites of copper oxide nanoparticles immobilized on microcrystalline cellulose (Cu2O@MCC) were synthesized and studied for their catalytic activity toward 1,3‐dipolar cycloaddition reaction. Azomethine ylide was in situ generated from isatin and 1,2,3,4‐tetrahydroisoquinoline (THIQ) and styrylisoxazoles/chalcones used as dipolarphiles in one‐pot synthesis of novel spiro polycyclic heterocyclic compounds. Cu2O@MCC showed excellent catalytic activity on 20 mg of composite with 30% loading of copper on MCC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Chowhan et al synthesised copper oxide NPs immobilised on microcrystalline cellulose (Cl-Cu-3) and used it for the synthetic construction of spiro polycyclic heterocyclic compounds (22/24) from isatin (20), 1,2,3,4-tetrahydroisoquinolines (21) and styrylisoxazoles (19) or chalcones (23) as dipolarophiles via azomethine ylide generation in 87-97% yield (Scheme 5). 60 The synthesis of the catalyst was accomplished by following the reported protocol using microcrystalline cellulose and copper sulfate pentaydrate.…”
Section: Scheme 4 Cu 2 O@mham Catalysed Synthesis Of Isoquinolones 18mentioning
confidence: 99%
See 1 more Smart Citation
“…Chowhan et al synthesised copper oxide NPs immobilised on microcrystalline cellulose (Cl-Cu-3) and used it for the synthetic construction of spiro polycyclic heterocyclic compounds (22/24) from isatin (20), 1,2,3,4-tetrahydroisoquinolines (21) and styrylisoxazoles (19) or chalcones (23) as dipolarophiles via azomethine ylide generation in 87-97% yield (Scheme 5). 60 The synthesis of the catalyst was accomplished by following the reported protocol using microcrystalline cellulose and copper sulfate pentaydrate.…”
Section: Scheme 4 Cu 2 O@mham Catalysed Synthesis Of Isoquinolones 18mentioning
confidence: 99%
“…BET revealed the dimension of MNPs in the range of (83), ammonium acetate (95), different aldehydes (88) and ethyl acetoacetate (154), catalysed via the Hantzsch reaction with ethanol as the solvent in excellent yields (91-95%).The catalyst retained its activity for five successive runs. The authors reported the successful synthesis of quinazolines using substituted benzaldehyde, dimedone, and urea using the same catalysts in ethanol at 60 102 Sulfonic acid functionalised silicacoated CoFe 2 O 4 NPs were synthesised using the co-precipitation method, and then altered with chlorosulfonic acid. The catalyst retained its efficiency for five cycles without any significant changes.…”
Section: Scheme 47 Cufe 2 O 4 Np Catalysed Annulation Of 151 With 152mentioning
confidence: 99%
“…92,93 Although previously published approaches using a homogenous catalyst for preparing spiro derivatives are valuable, these catalysts suffer from some disadvantages, such as high cost, drastic separation from the reaction mixture, long-duration reaction, and high temperature. [94][95][96][97][98][99] Over recent years, various heterogenized organic polymer catalysts based on helical polymers (single-handed helical polyisocyanides), 100 polyethyleneglycols (PEG-Ni NPs, PEG-OSO 3 H), 101,102 polystyrene (PS@GO-Fe 3 O 4 ), 86 chitosan (Fe 3 O 4 @CS-SO 3 H NPs, Bmim(OH)/chitosan/C 2 H 5 OH), 103,104 cellulose (cellulose-SO 3 H, nano-cellulose-SbCl 5 , Cu 2 O@MCC, NiII(BAPTE)(NO 3 ) 2 -Cell nanocatalyst), [105][106][107][108] polyaniline (PANI/ Fe 3 O 4 /CNT), 109 and collagen protein (Fe 3 O 4 @SiO 2 /ECH/IG) 110 have been used in the synthesis of spiro-fused[4H-pyran]. Although the above-mentioned catalytic systems can be readily separated, the recycling times were low (probably due to leaching or tedious workup).…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds are among the most versatile organic compounds in natural and biologically active synthetic materials, pharmaceuticals, and synthetic intermediates (Bur and Padwa, 2004;Dwivedi et al, 2020;Borah et al, 2021a;Borah and Chowhan, 2021;Kumar B. et al, 2022). The basic unit of heterocycles comprises a ringed structure with a heteroatom like nitrogen, oxygen, or sulfur, other than carbon, and the properties of the compound depend significantly on the number and types of heteroatoms present in the ring.…”
Section: Introductionmentioning
confidence: 99%